"Hepatic Superscan" in a Patient With Hepatosplenic Alphabeta T-cell Lymphoma: 18F-FDG PET/CT Findings. (August 2018) - Liu, Entao; Wang, Siyun; Lai, Peilong; Lian, Zhouyang; Wang, Shuxia
Abstract : Abstract: A 36-year-old woman with a 2-week history of fever and markedly elevated lactate dehydrogenase levels. Nonenhanced CT and contrast-enhanced CT showed hepatosplenomegaly, diffusely decreased attenuation of the liver, and homogeneous enhancement in the hepatic and splenic parenchyma. 18 F-FDG PET/CT revealed diffuse intense heterogeneous uptake by the liver (like superscan in bone scintigraphy). A liver needle biopsy confirmed the diagnosis of hepatosplenic alphabeta T-cell lymphoma. Subsequently, she received chemotherapy. The follow-up 18 F-FDG PET/CT showed decreased 18 F-FDG uptake in the liver and spleen.